State of the practice for mesh generation and mesh processing software. (October 2016) - Spencer Smith, W.; Adam Lazzarato, D.; Carette, Jacques
Highlights: The state of software development practices for mesh generation and mesh processing software is assessed. Some concerns identified for the software qualities of maintainability, usability, reusability and performance. Recommendations provided. Abstract: We analyze the state of development practices for Mesh Generation and Mesh Processing (MGMP) software by comparing 27 MGMP projects. The analysis employs a reproducible method based on a grading template of 56 questions covering 13 software qualities. The software is ranked using the Analytic Hierarchy Process (AHP), a multicriteria decision making method appropriate for cases with a mix of qualitative and quantitative factors. The results reveal concerns regarding the maintainability, usability, reusability and performance of some MGMP software. Five recommendations are presented as feedback to the MGMP community: (i) Use an issue tracker for bug management and support requests. (ii) Document performance measures. (iii) Increase the use of libraries to promote software re-use to avoid "re-inventing the wheel." (iv) Improve reproducibility by recording the set up details for the development and testing environments. (v) Improve confidence in correctness through requirements specification, formal specification languages, and automated testing.